Transforming Systems for Parental Depression and Early Childhood Developmental Delays Findings and Lessons Learned from the Helping Families Raise Healthy Children Initiative - Schultz, Dana (RAND Corporation, 2013)
The Helping Families Raise Healthy Children initiative addressed depression among parents of children with early childhood developmental delays, aligning the early intervention and behavioral health systems with a focus on relationship-based care. The initiative focused on identification of at-risk families, referral, and engagement in services that addressed the needs of parents and young children in the context of their relationship.